A Case of Pulmonary Carcinoid Tumor with a Superimposed Aspergilloma Presenting As a Covert Ectopic Adrenocorticotropic Hormone Syndrome - Kim, Kyoung Jin; Yu, Ji Hee; Kim, Nan Hee; Kim, Young Hye; Kim, Young Sik; Seo, Ji A (Frontiers in Endocrinology, 2017)
Ectopic adrenocorticotrophic hormone (ACTH) syndrome is a challenging diagnosis only responsible for approximately 10% of Cushing syndrome cases. It has been associated with a variety of benign and malignant tumors including a carcinoid tumor accompanied by aspergilloma in our case that was significantly difficult to be detected. We report a 79-year-old woman with uncontrolled hypertension and hypokalemia presenting with generalized edema. Her laboratory results revealed ACTH-dependent Cushing syndrome, but imaging studies did not show any discrete lesions secreting ACTH. Her petrosal to peripheral ACTH gradient resulted in no evidence of pituitary adenoma. As the only lesion suspicious for ectopic ACTH secretion was a right lower round cystic lesion that did not appear to be a carcinoid tumor on computed tomography scan of the chest, the patient underwent video-assisted thoracic surgical resection to provide a definitive diagnosis. The final diagnosis was a small ectopic ACTH-secreting carcinoid tumor with unusual superimposed aspergilloma in the periphery of the lung. Postoperatively, the abnormal endocrine levels were normalized, and all of the clinical symptoms and signs were ameliorated. This is an informative case of ectopic ACTH syndrome that was the cause of hypokalemia, hypertension, metabolic alkalosis, and hypercortisolism despite its poorly specific cushingoid morphology and uncommon imaging findings. Therefore, we recommend that clinicians investigate any possible lesion as a potential source of ectopic ACTH syndrome.